Evaluasi Program Pendidikan Inklusi di SD Bali Hati - I.P Suasta Yasa; D.G.H Divayana; N.L.G Erni Sulindawati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to determine the results of the evaluation separately or together in the context, input, process, product and constraints that occur in the implementation of the inclusion education program for children with special needs in SD Bali. This research is a program evaluation research with the CIPP model. The population in this study is class teachers (homeroom teachers), parents of students, subject teachers and GPK teachers. The sample determination in this study used purposive sampling techniques, with a total sample of 33 people consisting of class teachers (homeroom teachers), parents, subject teachers and GPK teachers. Data context, input, process and product in this study were collected by questionnaire using Likert scale 1-5. The data analysis method used in this study is a quantitative descriptive analysis method. To determine the effectiveness of the implementation of the inclusion education program at SD Bali Hati, the raw score is transformed into a Z score then into a T-Score then verified into the Glickman Quadrant. Based on the research that has been done, it was found that: 1) the implementation of the inclusion education program in SD Bali in terms of the context component is classified as effective, 2) the implementation of the inclusion education program in SD Bali in terms of the input component is classified as effective, 3) the implementation of the inclusion education program in SD Bali in terms of the process component is classified as effective, 4) the implementation of the inclusion education program in SD Bali in terms of the product component is classified as effective, 5) the results of the evaluation of the implementation of the inclusion education program in SD Bali in terms of the components of context, input, process and product obtained effective results.